2020
DOI: 10.32939/ejrpm.v3i2.595
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Realistic Mathematics Education Approach on Mathematical Problem Solving Ability

Abstract: Abstract. The improvement of mathematical problem-solving ability was the aim of this study through the application of the Realistic Mathematics Education approach compared to conventional learning according to the students' self-efficacy level. This study used a quasi-experimental study with a static group design conducted in eighth-grade students at SMP Negeri 1 Kerinci and SMP Negeri 5 Kerinci. Data collected through the questionnaire to determine students’ self-efficacy level and the test of students’ math… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
0
0
2
Order By: Relevance
“…The results in this study follow the findings of previous research which found that RMEbased learning is effective in improving mathematical problem-solving abilities (Anggraini & Fauzan, 2020;Musdi et al, 2023;Widana, 2021). Other research also shows that problemsolving abilities with RME learning are better than conventional (Mukaromah et al, 2023).…”
Section: Discussionsupporting
confidence: 89%
“…The results in this study follow the findings of previous research which found that RMEbased learning is effective in improving mathematical problem-solving abilities (Anggraini & Fauzan, 2020;Musdi et al, 2023;Widana, 2021). Other research also shows that problemsolving abilities with RME learning are better than conventional (Mukaromah et al, 2023).…”
Section: Discussionsupporting
confidence: 89%
“…When a student has a high level of curiosity and interest in learning, it will automatically hone the student's ability to understand a problem and solve the problems that have been found (Darling-Hammond et al, 2020); (Javaid et al, 2023). Based on the explanation above, it can be said that these things are what causes learning using mathematics e-modules which are integrated with Islamic values to be able to improve students' ability to solve problems mathematically (Rakhmawati, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Peran guru dalam pendekatan RME sebagai fasilitator, moderator, dan evaluator (Hadi, 2017). RME membantu guru mengajarkan matematika kepada siswa dan juga berhasil meningkatkan kemampuan pemahaman matematika (Febriyanti et al, 2019); (Sedaryati, 2020); (Sholikhah & Rasmita, 2020), kemampuan pemecahan masalah (Anggraini & Fauzan, 2020), kemampuan literasi matematika (Istiana & Satianingsih, 2020), kemampuan spasial matematika (Yustiana et al, 2020).…”
Section: Pendahuluanunclassified